Automatic Versus Manual Solar Panel Cleaning for Remote Locations - Lamont, Lisa Ann; Chaar, Lana El (Journal of Technology Innovations in Renewable Energy, 2013)
Photovoltaic solar technology is now being widely investigated for implementation in the UAE as a possible renewable energy source. Currently the main emphasis is on the accessible areas but remote locations are now being explored for the possibility of large scale deployment. However due to the environment and location certain measures such as regular cleaning must be considered to ensure the efficient operation of the PV panels. This paper investigates the cost of current developed cleaning technologies available in the Gulf region, highlights their advantages and disadvantages and the time needed to recoup initial investment.